Pengaruh Senam Ergonomic Terhadap Intensitas Nyeri Osteoarhtritis Lutut Pada Lansia Di Kecamatan Wonoasih Kota Probolinggo - Kholisotin, Kholisotin; Hasanah, Ira Dhatul; Qanitah, Niswah Nilam (Jurnal Keperawatan Muhammadiyah, 2021)
Joint pain is characterized by swelling in the joints, the presence of redness, feeling hot, pain will cause interference with the motion system. In this condition the elderly are often disturbed, if more joints are attacked. Ergonomic gymnastics is an effort to reduce pain with nonpharmacological therapy. The purpose of this study was to determine the effect of ergonomic gymnastics on the scale of joint pain in elderly women in the area of in the wonoasih sub district of the city probolinggo. The design of this study used a Quasy-experimental design pre test and post test design. In this study the total population was all elderly in the in the wonoasih sub district of the city probolinggo as many as 90 people, and the number of samples used was 70 respondents. The technique used in sampling is simple purposive sampling. The instrument of data collection is using a observation sheet. The method of data analysis in this study is the Wilcoxon test (p 0.05). The results of the study prove that joint pain before ergonomic exercise is mostly categorized as uncontrolled severe pain scale as many as 35 people. Joint pain after ergonomic exercise was mostly classified as non-pain as many as 35 people. The Wilcoxon test results obtained a significant value of 0,000 (p value â‰¤ 0,05) which means that there is the effect of ergonomic exercise on the scale of joint pain in elderly women in the wonoasih sub district of the city probolinggo. Suggestions in this study are expected to the elderly to reduce the frequency of pharmacological treatment and more non-pharmacological treatments such as ergonomic exercise because prolonged pharmacological treatment can bring side effects such as dependence on drugs taken.